Elaboración e implementación de un software educativo para la enseñanza-aprendizaje de la asignatura de ciencias sociales para los estudiantes del séptimo año de educación general básica, de la escuela fiscal Miguel Riofrío # 1 de la ciudad de Loja, periodo 2013 -2014 - Farez Castillo, Diana Jacqueline (2016)
The present work was made in the city of Loja, Miguel Riofrío School # 1 with the teaching of the subject Social Sciences, making use of the materials used to teach students from the seventh year of basic education, such as: textbook, student workbook and teacher awarded by the Ministry of Education of Ecuador. To narrow the issues techniques for collecting information was used as: survey of students in the seventh year of basic education, written teachers of the subject of Social Sciences interview, which made it possible to obtain the necessary information and come to the conclusion the need for teaching materials, to allow the teaching of social sciences making use of it to strengthen teaching and more interesting, different and meaningful to students who have had difficulty achieving reach with his knowledge. In addition, it takes into account the theoretical framework being helpful throughout the process. To develop the teaching materials, the Waterfall Methodology which has five phases was applied , allowing to have a good development of educational software , which has as main characteristics their interaction with the content, incorporating activities and assessments, as well as videos related to ace thematic implemented . In conclusion, the present Education Software will be used as teaching aids in the teaching-learning process for students in seventh year helping to better understanding of the subject.